The Role of Online Food Delivery Services in the Competitiveness of the Yogyakarta Culinary Industry during the Covid-19 Pandemic - Dariya Nawar Salma; Rini Rachmawati (Faculty of Geography, Universitas Gadjah Mada, 2022)
Culinary business actors in the culinary industry at Yogyakarta provide Online Food Delivery Services to facilitate the trade. This study, therefore, aims to identify the benefits of Online Food Delivery Services as well as the market reach from the providers’ point of view, and further analyzes the intrinsic role played in increasing competitiveness in the culinary industry of Yogyakarta during the Covid-19 pandemic. The process involved a qualitative method, where data was collected through semi-structured interviews, observation, and documentation. Subsequently, qualitative descriptive analysis techniques were used for analysis. Based on the study results, online food delivery services were determined to be beneficial in terms of effectiveness and efficiency in performance, organizational structure, and strategic and competitive advantage. The providers reportedly reached markets at distances up to 25 km–30 km. These actors play a significant role in increasing the competitiveness of the creative industry, particularly in the culinary sub-sector in Yogyakarta City during the pandemic. Moreover, this assumption is based on aspects of competition between similar companies, where the bargaining power of buyers, the threat of new entrants and substitute products were significant.